Influence of input power in Ar/H2 thermal plasma with silicon powder by numerical simulation - Yulianta Siregar; Yasunori Tanaka; Yoshihiko Uesugi; Tatsuo Ishijima (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Numerical simulation in inductively coupled thermal plasma was made on the temperature distribution in argon (Ar)+hydrogen (H2) induction thermal plasma torch with silicon (Si) powder injection to obtain the temperature distribution and gas flow fields. The ICTP model was used in this research because it has benefit of good repeatability and no contamination process. Interactions between ICTP and injected powder are very complicated to be understood only by related experiments. Influence of input power in ICTP was numerically investigated on thermal plasma temperature fields and powder evaporation. The temperature distributions of thermal plasma and Si vapor distribution were compared at input powers of 20 kW, 30 kW, and 40 kW. Results indicated that higher input power increases the temperature of the thermal plasma with doughnut shape but it slightly enhances evaporation of the powder at the center axis of the plasma torch.